Development of an Automatic Coupler for Railway Vehicles: A Topology Optimization Approach with Numerical and Experimental Validation - Jean Mario Valentino; Agus Sigit Pramono; Achmad Syaifudin; Lukman Shalahuddin; Mustasyar Perkasa; Katsuhiko Sasaki (Automotive Experiences, 2024)
Topology optimization has demonstrated its effectiveness in generating lightweight and structurally efficient designs. This study focuses on refining the geometry of an automatic coupler body for trains using solid isotropic material with penalization and a level set method. These optimization methods are applied to the numerical model of the automatic coupler, and their results are compared to select the optimal design. The tensile strength of the automatic coupler is examined through numerical simulations and validated by experimental tensile tests conducted on a 1:1 scale prototype. The optimization outcomes reveal a remarkable 46.41% reduction in the mass of the automatic coupler body compared to the initial model. An evaluation of the tensile strength of the prototype demonstrates the ability of the automatic coupler to withstand the primary load without undergoing plastic deformation. Furthermore, a strong correlation is observed between the numerical and experimental results. This research contributes to advancing the design of next-generation automatic couplers, emphasizing the crucial aspects of lightweight design and structural performance.